Literacy Activities as the Role of Library to Improve Character Education in Binjai City Library Office - Mulanda, Wida; Nurhayani, Nurhayani (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
One of the library roles becomes a place of learning resources for the community. In addition, the library also plays a role in providing a place to learn for children in the context of character education. This study aims to determine how the role of library to help the improvement of children's character education. This study uses descriptive qualitative research techniques and data collection techniques through observation, interview, and documentation. In this study, we employed data validity test through source triangulation and triangulation techniques. Analysis data used refers to the Miles and Huberman models. This study involved eight informants, consisting of: one Librarian, four library staff, one storyteller, one teacher, and one parent who participated in literacy activities. The results of this study indicates that the library has a role in supporting the growth and development of children, particularly in character development, namely: 1) providing a place for children to learn inside and outside the library, 2) improving character education by reading tourism activities, 3) building the quality of children's literacy and instilling character values through toddler park reading corner activities. According to the research findings from the data obtained from interviews with informants, it reveals that the library roles help to improve character education in Binjai City Library. It can be evidenced from the literacy activities carried out by the library.